Does head start improve children's life chances? Evidence from a regression discontinuity design - Jens Ludwig; Douglas L. Miller (Institute for the Study of Labor (IZA), 2006)
This paper exploits a new source of variation in Head Start funding to identify the program's effects on health and schooling. In 1965 the Office of Economic Opportunity (OEO) provided technical assistance to the 300 poorest counties to develop Head Start proposals. The result was a large and lasting discontinuity in Head Start funding rates at the OEO cutoff for grant-writing assistance. We find evidence of a large drop at the OEO cutoff in mortality rates for children from causes that could be affected by Head Start, as well as suggestive evidence for a positive effect on educational attainment.
Keywords: I18; I20; I38; 330; early childhood education; poverty; schooling; health; Head Start; Kinderbetreuung; Gesundheitspolitik; Armutspolitik; USA